ANALISIS PENGARUH VOLUME TRANSAKSI UANG ELEKTRONIK, INFLASI DAN PERTUMBUHAN EKONOMI INDONESIA DENGAN PENDEKATAN VECTOR ERROR CORRECTION MODEL PERIODE 2014Q1 – 2024Q1 - Hafis Al Ahzad, Muhammad; Restikasari, Wenny (Jurnal Bina Bangsa Ekonomika, 2025)
Economic growth is one of the focus of achievements that almost all countries continue to pursue. The benchmark for the success of a country in building its economy is to use the amount of economic growth. Inflation is one of the variables that can affect economic growth even though there are many different views on inflation having a positive or negative effect on economic growth. In addition to inflation, economic growth is also influenced by technological advances such as the emergence of e-money. The practicality of using e-money attracts people to shop, this is what can increase economic growth figures. This study aims to determine the long-term and short-term effects between variables, namely the volume of electronic money transactions (e-money), inflation and economic growth in Indonesia from the first quarter of 2014 to the first quarter of 2024. This study uses a type of quantitative research using secondary data obtained from the Central Statistics Agency and Bank Indonesia. The research method used is the Vector Error Correction Model. This method has several stages of analysis tests, namely stationarity test, optimal lag test, stability test, cointegration test, VECM estimation test, impulse response function test and variance decomposition test. The results of this study state that inflation variables have a positive and significant effect in the long term on economic growth and e-money, e-money variables have a significant effect in the short term on economic growth and economic growth variables have a significant effect in the short term on inflation variables in Indonesia for the period 2014 first quarter to 2024 first quarter.